2019
DOI: 10.1093/europace/euz283
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aspiration of large pacemaker and implantable cardioverter-defibrillator lead vegetations facilitating safe transvenous lead extraction

Abstract: Aims Treatment of patients with systemic cardiac implantable electronic device (CIED) infection with large lead vegetations is challenging and associated with relevant morbidity and mortality. To avoid complications from open surgical extraction, a novel approach with percutaneous aspiration of large vegetations prior to transvenous lead extraction was instituted. The results of this treatment concept were retrospectively analysed in this multicentre study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…In 2014, the US Food and Drug Administration approved the AngioVac system for the removal of unwanted intravascular materials (thrombi and emboli). A recent study of the AngioVac system by Starck and colleagues 14 reported 101 cases of cardiac device-related infective endocarditis patients who underwent aspiration of large vegetations (mean size 30.7 6 13.5 mm) followed by transvenous lead removal that showed complete procedural success of 94%. It also showed a very high success rate in using AngioVac prior to infected lead extraction, which further supports the use of percutaneous aspiration as highly effective and safe, with a low complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, the US Food and Drug Administration approved the AngioVac system for the removal of unwanted intravascular materials (thrombi and emboli). A recent study of the AngioVac system by Starck and colleagues 14 reported 101 cases of cardiac device-related infective endocarditis patients who underwent aspiration of large vegetations (mean size 30.7 6 13.5 mm) followed by transvenous lead removal that showed complete procedural success of 94%. It also showed a very high success rate in using AngioVac prior to infected lead extraction, which further supports the use of percutaneous aspiration as highly effective and safe, with a low complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…1 A potential advancement in this area is the novel use of vacuum-assisted aspiration devices to remove or significantly debulk lead-associated vegetations before percutaneous extraction. [3][4][5][6] This new management option is especially appealing in light of the increasing need for lead extractions in older patients and those with more comorbidities, who may not tolerate surgical management. 7 Although there is a number of available percutaneous devices that can remove intravascular or intracardiac thrombus, vegetations, or masses, the AngioVac system has a large inflow cannula that was well suited to handle the sizable vegetation encountered in this case.…”
Section: Discussionmentioning
confidence: 99%
“…TEE guidance is particularly helpful for improving the safety of the procedure, given the limited steerability of the AngioVac cannula. 4 Last, intraprocedural TEE guidance allows real-time detection of procedural complications such as pulmonary emboli and iatrogenic valvular or other tissue injury, which may require additional management. Findings such as residual vegetation or the presence of ghosts have both therapeutic (longer duration of antibiotic therapy) and possibly prognostic (increased mortality) implications.…”
Section: Discussionmentioning
confidence: 99%
“…Since pulmonary embolization of vegetations during lead extraction may result in subsequent sepsis various interventional techniques to reduce the size of vegetations have been evaluated including the use of basket catheters for "vegectomy" 3 or systemic thrombolysis 4 . Recently, a transcatheter aspiration system based on an extracorporal circuit in a veno-venous configuration (AngioVac, Angiodynamics, Latham, NY, USA) using a specialized filter has been introduced and is successfully used in an increasing number of patients 5 . However, this system has limitations such as need for therapeutic anticoagulation during the procedure and high healthcare costs.…”
Section: General Informationmentioning
confidence: 99%